The long-lasting effect of feudal human capital: Insights from Vietnam - Trung Xuan Hoang; Cuong Viet Nguyen (Global Labor Organization (GLO), 2024)
This study investigates the long-term effect of the density of the elite - the highest educated - during the period 1075-1919 on today's educational attainment and economic performance in Vietnam. Using nearly 20,000 elites, including 17,061 junior bachelors and bachelors, and 2,895 doctors who passed the imperial examination (1075-1919), and the distance to the nearest examination centers as an instrumental variable, we find that elite density has persistent effects on the present-day educational attainment, income, poverty, and night-time light intensity. The impact of the elite density on schooling years tends to be higher in urban areas than in rural areas. Our findings are robust to a variety of model specifications.
Keywords: I25; O12; E24; N35; 330; Human capital; historical legacy; economic growth; household income